bahasa inggris - Asep Yanuar Arifin; Atik Djayanti (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
This study examines the determinants of firm value in the Indonesian palm oil plantation sector, focusing on the role of biological asset intensity and crude palm oil productivity. The background of this research lies in the strategic importance of the plantation industry and the need to understand how internal operational factors influence market valuation under dynamic economic conditions . The study uses secondary data derived from annual financial statements of 12 plantation companies listed on the Indonesia Stock Exchange over the period 2019–2024, resulting in 72 observations. A quantitative approach is applied using panel data regression analysis to evaluate the relationships between variables. The results reveal that biological asset intensity has a negative and statistically significant effect on firm value, indicating that higher proportions of such assets may increase earnings volatility and perceived risk, thereby reducing investor confidence . In contrast, crude palm oil productivity shows a positive and significant effect, suggesting that improved operational efficiency enhances financial performance and firm valuation. Simultaneously, both variables significantly influence firm value, with the model explaining a moderate proportion of variation. In conclusion, firm value in the plantation sector is not solely determined by the scale of biological assets but by the efficiency of their utilization. Enhancing productivity is crucial for value creation, while effective asset management is necessary to mitigate associated risks and sustain investor confidence. Keywords: Biological Asset, CPO Productivity, Firm Value, Plantation, Data Panel